EVALUATION OF THE DISCOMFORT LEVEL IN THE REMOVAL OF TONGUE COATING - Moccelin, Camila; Marinho, Suzana; Lima Machado, Débora; Pereira Butze, Juliane (Health and Society, 2021)
Aim: The main objective of this study was to analyze which tongue cleaning technique to remove the tongue coating causes less discomfort/anxiety to the patient. Methodology: The study selected patients treated at the Clinic of Centro Universitário da Serra Gaúcha-FSG between the months of May and October 2018. The patients were randomized so that each one of them went through the three groups, receiving different hygiene instruction techniques language in each group. Three techniques were analyzed: with a multi-bristled toothbrush, with gauze and with a tongue scraper. The degree of anxiety for each method was evaluated through a questionnaire. Results: With the toothbrush, 3.4% of the patients had mild vomiting, 40% moderate and 56.6% strong/strong degree. With gauze, 20% of the participants had a mild degree of anxiety, a moderate degree of 73.3% and a very/strong degree of 6.7%. With the tongue scraper, 53.3% of the sample had a mild degree of anxiety, a moderate degree of 40% and a very/strong degree of 6.7%. All participants reported feeling anxious about all the techniques performed, however the technique that generated the least discomfort was the technique performed with the tongue scraper. Conclusion: Based on the data analysis of this study, the patients presented different degrees of anxiety in face of all the tongue hygiene techniques used, however, the technique that generated the least discomfort was the one that used the tongue scraper as a hygiene instrument.